PENINGKATAN KREATIVITAS ANAK 5-6 TAHUN MELALUI METODE DISCOVERY LEARNING MENGGUNAKAN BAHAN ALAM DI TK KARTIKA II.3 PALEMBANG - Sindy Agustina Arista; Yin Yin Septiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was prompted by the low creativity of children at Kartika II.3 Kindergarten in Palembang due to monotonous conventional learning. The study aims to enhance the creative potential of children aged 5-6 through the method.discovery learningassisted by exploratory natural materials media. Using a Classroom Action Research (CAR) approach in two cycles, the study involved 15 children as subjects. Data were analyzed through systematic observation of the originality of students' ideas and work. The findings showed a significant surge in the subjects' creative capacity: from 6.64% in the initial stage, increasing to 13,13% in Cycle I, and reaching 80% in Cycle II in the Very Well Developed (BSB) category. These results confirm that the synergy of the independent discovery method and environmental media effectively optimizes divergent thinking and learning independence, while providing strategic implications for pedagogical innovation in early childhood education.